(untitled) (Journal of Human Sciences, 2024)
The research addresses the intellectual vision of Sheikh Anta Diop, who believes that Africa is the cradle of humanity, that everything began in Africa, that Egyptians and Africans descend from the same ancestors, and that the ancient Egyptian civilization was essentially an African Negro civilization. This is due to the close links between the West African Wolof languages and the ancient Egyptian languages. Anta Diop says that Egyptian civilization is for Africans what Greek civilization is for the West, and that the origins of Hellenic civilization were located in Black Africa, which produced thought and science and influenced the emerging intellectual and philosophical movement in Greece. Ancient times, refuting the Western point of view that the West is the origin of human civilization and its human achievements.